2022
DOI: 10.1155/2022/2262289
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Seismic Response of Long‐Span Special Steel Truss Cable‐Stayed Bridge

Abstract: Due to the small self-weight of the steel truss cable-stayed bridge with a single tower and a single cable plane, the torsional stiffness and wind stability of the structure are reduced. The arrangement of the deck type makes the mechanical properties of the cable-stayed bridge more complicated while reducing the cost and increasing the aesthetics. The effects of structural parameter variations and traveling wave effects on the seismic response of this steel truss cable-stayed bridge with a single tower and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the assessment of the fatigue life of metallic structures, many studies have been conducted and a many achievements have been made. Based on the fatigue crack expansion of metallic materials, the mathematical model of the fatigue crack expansion, as shown in Figure 3, was obtained [13,14]. As can be seen in Figure 2, the initial crack Type I stress intensity factor is symmetrically distributed, with larger values at the middle of the crack leading edge (short semi−axial crack tip) and at the ends of the long semi−axis, with a maximum value of up to 77.67 MPa.mm 1/2 , which shows that the initial crack expands relatively quickly at the ends of the long and short semi−axes; the stress intensity factors of Type II and Type III fluctuate around 0 MPa.mm 1/2 , which is much smaller than the stress intensity factors for Type II and Type III, which fluctuate around 0 MPa.mm and are much smaller than those for Type I.…”
Section: Fatigue Life Assessment Methods Based On Fracture Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the assessment of the fatigue life of metallic structures, many studies have been conducted and a many achievements have been made. Based on the fatigue crack expansion of metallic materials, the mathematical model of the fatigue crack expansion, as shown in Figure 3, was obtained [13,14]. As can be seen in Figure 2, the initial crack Type I stress intensity factor is symmetrically distributed, with larger values at the middle of the crack leading edge (short semi−axial crack tip) and at the ends of the long semi−axis, with a maximum value of up to 77.67 MPa.mm 1/2 , which shows that the initial crack expands relatively quickly at the ends of the long and short semi−axes; the stress intensity factors of Type II and Type III fluctuate around 0 MPa.mm 1/2 , which is much smaller than the stress intensity factors for Type II and Type III, which fluctuate around 0 MPa.mm and are much smaller than those for Type I.…”
Section: Fatigue Life Assessment Methods Based On Fracture Mechanicsmentioning
confidence: 99%
“…In the assessment of the fatigue life of metallic structures, many studies have been conducted and a many achievements have been made. Based on the fatigue crack expansion of metallic materials, the mathematical model of the fatigue crack expansion, as shown in Figure 3, was obtained [13,14]. As can be seen in Figure 3, crack expansion can be divided into three stages.…”
Section: Fatigue Life Assessment Methods Based On Fracture Mechanicsmentioning
confidence: 99%
“…For example, nonlinear time course analysis and nonuniform seismic analysis are used to study the influence of structural parameter changes and traveling wave effects on the seismic response of steel truss cable-stayed bridges with a single tower and a single-cable plane. It was concluded that the influence of the variations of steel truss beam stiffness parameters on the structural internal force of single-tower, single-surface steel truss girder cable-stayed bridges is not prevalent [22]. A double-pylon cable-stayed bridge with a single-cable plane and steel truss girder with a similar structure to the research object of this paper was investigated regarding the influence of a stayed cable surface arrangement, the concentration of the dead load and structural system on the dynamic characteristics of a double-pylon cable-stayed bridge with a single-cable plane and steel truss girder through the dynamic load test [23].…”
Section: Introductionmentioning
confidence: 99%
“…Las ondas sísmicas pueden afectar áreas lejanas en minutos (Yong et al ,2022). El comportamiento sísmico de los puentes varía seg ún su dise ño (Chenchen et al ,2023).…”
Section: Introducci óNunclassified
“…El comportamiento sísmico de los puentes varía seg ún su dise ño (Chenchen et al ,2023). Puentes bien equilibrados y dise ñados son más fáciles de proteger contra terremotos (Yong et al ,2022), pero estructuras no estándares pueden ser más vulnerables y pueden necesitar análisis detallados (Cheng-Qi et al ,2022). Por ejemplo, el Puente de la Bahía de San Francisco-Oakland sufri ó da ños en el terremoto de Loma Prieta en 1989 (Chen & Duan ,2014).…”
Section: Introducci óNunclassified